2022
DOI: 10.3390/nu14091944
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Nutritional Intakes in Italian Pregnant Women in Comparison with National Nutritional Guidelines

Abstract: Background: Nutritional quality during pregnancy is crucial for mother and child health and their short/long-term outcomes. The aim of this study is to evaluate the adherence to nutritional recommendations in Italy during the three pregnancy trimesters in Normal Weight (NW) and Over Weight (OW) women. Methods: Data from a multicenter randomized controlled trial included 176 women (NW = 133; OW = 43) with healthy singleton pregnancies enrolled within 13 + 6 weeks of gestation. Dietary intake was assessed every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…Thirdly, the actual intake of micronutrients of the participants in the present study failed to meet the recommendations, which is similar to several previous studies in GDM women or normal glucose tolerance pregnant women [24][25][26], even though their total dietary energy intake was adequate. This indicates that the dietary quality of the study participants was not optimal.…”
Section: Discussionsupporting
confidence: 81%
“…Thirdly, the actual intake of micronutrients of the participants in the present study failed to meet the recommendations, which is similar to several previous studies in GDM women or normal glucose tolerance pregnant women [24][25][26], even though their total dietary energy intake was adequate. This indicates that the dietary quality of the study participants was not optimal.…”
Section: Discussionsupporting
confidence: 81%
“…Nutrient intakes from 7-DRs showed a worrying distance from recommendations, despite the reported energy intake being lower than the recommended in both total study population and subgroups. In line with this result, we recently recorded energy intakes lower than recommended in a cohort of Italian normal-and overweight pregnant women [21]. The Mediterranean PHIME cohort additionally confirmed this result and the authors suggested that pregnant women did not show any energy deficit, probably due to the combination of inadequate eating habits and low physical activity level [10].…”
Section: Discussionsupporting
confidence: 75%
“…Each frequency consumption was reported as a factor, derived from the ratio of the frequency per day, week and month each food item was consumed, in order to obtain a daily fraction of consumption for each item. A dietary bromatological analysis was performed on the obtained data, as previously reported [21]. Macro-and micronutrient intakes were assessed by us using Food Composition Database for Epidemiological Studies in Italy (Banca Dati di Composizione degli Alimenti per Studi Epidemiologici in Italia-BDA) [22].…”
Section: Nutritional Data Collectionmentioning
confidence: 99%
“…With the internet being more accessible to an increasing number of people, it could be thus assumed that easy access to information allows women to obtain all the necessary knowledge related to adequate nutrition, elimination of food risks, and nutritionrelated complications associated with pregnancy. However, studies show that this is far from the case and that women do not follow nutritional recommendations [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%